PENGARUH QUALITY OF WORKLIFE DAN KOMPETENSI TERHADAP KINERJA KARYAWAN (STUDI KASUS CV RGR INDRAKO SWALAYAN TELUK KUANTAN ) - Bimbi Mahdeta; Suryalena " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The objectives of this study were to analyze and find out the influence of quality of worklife to the employees performance, to analyze and find out the influence of competence to the employees performance and to analyze and find out the influence of Quality of Worklife and competence to the employees performance in CV RGR Indrako Swalayan Teluk Kuantan, located in Ahmad Yani Street, Kuantan Tengah district, Kuantan Singingi Regency Riau Province. The samples of this study were 46 employees of CV RGR Indrako Swalayan Teluk Kuantan and taken by census. The data analysis was done by SPSS ver. 20.0 by using validity and reliability test, determination test, t-test, F-test, simple regression, and multiple linear regression. This study found first, quality of worklife significantly influenced the employees performance in CV RGR Indrako Swalayan Teluk Kuantan. Second, competence significantly influeced the employees performance in CV RGR Indrako Swalayan Teluk Kuantan and third quality of worklife and competence significantly with simultanouesly influenced the employees perfomance in CV RGR Indrako Swalayan Teluk KuantanKeywords: Quality of worklife, competence, employees performance